2008
DOI: 10.1111/j.1524-4741.2008.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Limitations of Mammary Ductoscope in Management of Pathologic Nipple Discharge

Abstract: Mammary ductoscope allows visualization of the breast ductal wall and sampling of the abnormal area for diagnostic purposes. We are reporting our center experience in application of mammary ductoscope in detecting the underlying etiology of pathologic nipple discharge. Between November 2005 and December 2006 a total of 54 women, with spontaneous persistent nonlactational unilateral uniductal nipple discharge of no palpable lesions and negative breast sono-mammography, were included in the study for morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…While some researchers stated a significant correlation [27], others found no specific data, except for gross morphological abnormalities such as papillomas. Thus, visual inspection alone could not be sufficient to differentiate between benign and malign lesions [7,10].…”
Section: Ductoscopic Visual Diagnosis Sensitivity and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some researchers stated a significant correlation [27], others found no specific data, except for gross morphological abnormalities such as papillomas. Thus, visual inspection alone could not be sufficient to differentiate between benign and malign lesions [7,10].…”
Section: Ductoscopic Visual Diagnosis Sensitivity and Limitationsmentioning
confidence: 99%
“…Matsugana et al [34] showed the coexistence of intraductal papilloma in a major duct and ductal cancers separately in a peripheral duct. Denewer et al [27] found that the ductoscopic distance traveled was significantly related to histopathology. They did not find any malignant lesion within a depth of 2 cm.…”
Section: Ductoscopic Visual Diagnosis Sensitivity and Limitationsmentioning
confidence: 99%
“…Findings have shown cytology from ductal lavage during MD to be more useful than nipple squeeze or aspirate alone [2]. If the ductoscope does not reach smaller ducts, lavage fluid could be obtained from the TDLU within the same duct system.…”
Section: Histologic Specimensmentioning
confidence: 98%
“…In addition, MD can be performed easily as an office or out-patient diagnostic procedure with application of a local anesthetic (commonly lidocaine or xylocaine) by topical gel to the nipple or by periareolar infiltration or infusion down the cannulated nipple duct. Instillation of a local anesthetic into the nipple ducts after cannulation facilitates relaxation of the major duct muscle sphincters [1][2][3].…”
Section: Technology and Techniquementioning
confidence: 99%
“…However, further studies are required to define its role more clearly, as there are still limitations in clinical practice (8)(9)(10)(11)(12)(13)(14). Magnetic resonance imaging (MRI) may play an adjunctive role, aiding in the differentiation of benign ductal abnormalities from malignant ones (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%